Hypothenar hammer syndrome - Juscafresa, Laura Calsina; Grochowicz, Lukasz (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
In 1934 von Rosen first described a posttraumatic thrombosis of the distal ulnar artery resulting from blunt a trauma to the hypothenar region. But it was Conn in 1970 who named it the “hypothenar hammer syndrome (HHS)” 1–2.